2007
DOI: 10.1071/fp06287
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, anatomical and biochemical characterisation of photosynthetic types in genus Cleome (Cleomaceae)

Abstract: C4 photosynthesis has evolved many times in 18 different families of land plants with great variation in leaf anatomy, ranging from various forms of Kranz anatomy to C4 photosynthesis occurring within a single type of photosynthetic cell. There has been little research on photosynthetic typing in the family Cleomaceae, in which only one C4 species has been identified, Cleome gynandra L. There is recent interest in selecting and developing a C4 species from the family Cleomaceae as a model C4 system, since it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 24 publications
4
62
0
1
Order By: Relevance
“…GDC is thought to be absent in the M cells of well-developed C 2 species, perhaps as a result of a knockout mutation early in C 2 evolution (Rawsthorne, 1992;Sage et al, 2012). Consistently, GDCp is not observed in the M cells of many well-developed C 2 species, for example, in the genera Cleome (Marshall et al, 2007;Voznesenskaya et al, 2007), Euphorbia (Sage et al, 2011b), Brassica (Ueno, 2011), and Heliotropium (Muhaidat et al, 2011). In Flaveria spp., Hylton et al (1988) observed no significant immunogold labeling for GDCp in M cell mitochondria of the C 2 species Flaveria linearis and F. floridana.…”
Section: Photosynthesis In Flaveria Speciesmentioning
confidence: 66%
“…GDC is thought to be absent in the M cells of well-developed C 2 species, perhaps as a result of a knockout mutation early in C 2 evolution (Rawsthorne, 1992;Sage et al, 2012). Consistently, GDCp is not observed in the M cells of many well-developed C 2 species, for example, in the genera Cleome (Marshall et al, 2007;Voznesenskaya et al, 2007), Euphorbia (Sage et al, 2011b), Brassica (Ueno, 2011), and Heliotropium (Muhaidat et al, 2011). In Flaveria spp., Hylton et al (1988) observed no significant immunogold labeling for GDCp in M cell mitochondria of the C 2 species Flaveria linearis and F. floridana.…”
Section: Photosynthesis In Flaveria Speciesmentioning
confidence: 66%
“…Chloroplasts in the BS of C. gynandra are larger than those in the BS of C 3 species and, as in many other C 4 plants, are positioned in a strictly centripetal pattern (Marshall et al, 2007;Voznesenskaya et al, 2007). Transcripts derived from the GIANT CHLOROPLAST1 (GC1) gene were more abundant in C. gynandra than in C. spinosa (Table IV).…”
Section: Candidates For Additional C 4 -Related Genesmentioning
confidence: 93%
“…As a consequence, the Kranz anatomy was formed in which enlarged BS cells surrounded each vein and the BS cells were in turn surrounded by M cells. Within BS cells, organelle numbers were further increased (Muhaidat et al 2011;Marshall et al 2007;Sage et al 2011b;Voznesenskaya et al 2007). To re-utilize the photorespiratory CO 2 escaping from BS into M cells, the expression level of PEPC in the cytosol of the M cells were greatly enhanced.…”
Section: Gene Duplicationmentioning
confidence: 99%